2015
DOI: 10.1093/mnras/stv661
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in stellar superflares

Abstract: Two different mechanisms may act to induce quasi-periodic pulsations (QPP) in wholedisk observations of stellar flares. One mechanism may be magneto-hydromagnetic (MHD) forces and other processes acting on flare loops as seen in the Sun. The other mechanism may be forced local acoustic oscillations due to the high-energy particle impulse generated by the flare (known as 'sunquakes' in the Sun). We analyze shortcadence Kepler data of 257 flares in 75 stars to search for QPP in the flare decay branch or post-fla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 41 publications
(47 reference statements)
4
48
1
Order By: Relevance
“…A systematic study of QPPs in stellar white light flares was recently performed by Balona et al (2015); Pugh et al (2016). Typically, stellar QPP are seen as a periodic, decaying variation of the signal after the flare peak, which resembles SUMER oscillations in solar flares.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic study of QPPs in stellar white light flares was recently performed by Balona et al (2015); Pugh et al (2016). Typically, stellar QPP are seen as a periodic, decaying variation of the signal after the flare peak, which resembles SUMER oscillations in solar flares.…”
Section: Introductionmentioning
confidence: 99%
“…The similarity in solar and stellar flares, including the QPPs may give us hints to understand the nature of the flares and associated oscillations, as well as coronal plasma properties for various stars including the Sun (Balona et al 2015;Chang et al 2015). In particular, properties of oscillating loops could be estimated by applying an appropriate model to the frequency and amplitude modulation of the perturbation, which are independent on the sharpness and strength of the sources.…”
Section: Introductionmentioning
confidence: 99%
“…These pulsations, known as quasi-periodic pulsations (QPPs), are variations of flux as a function of time. Their nature has been examined in many previous studies of both solar (e.g., Parks & Winckler 1969;Kane et al 1983;Asai et al 2001;Fleishman et al 2008;Nakariakov & Melnikov 2009;Reznikova & Shibasaki 2011;Li et al 2015) and stellar (e.g., Balona et al 2015;Pugh et al 2016) observations. In a typical event, the emission from a solar flare is seen to pulsate with a characteristic timescale ranging from 1 s up to several minutes.…”
Section: Introductionmentioning
confidence: 99%
“…This not only implies a link between stellar flares and stellar magnetic activity but that the same physical processes are involved in solar and stellar flares. Balona et al [52] demonstrated that QPPs can be observed in Kepler flare light curves. Pugh et al [51] searched the entire Kepler short cadence database for flares with evidence of QPPs and Figure 10 shows an example of one such flare.…”
Section: The Seismology Of Stellar Flaresmentioning
confidence: 99%